2016
DOI: 10.1159/000440716
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Connectivity of the Insula and Nucleus Accumbens in Internet Gaming Disorder: A Resting State fMRI Study

Abstract: Aims: A possible addiction mechanism has been represented by altered functional connectivity (FC) in the resting state. The aim of this study was to evaluate the FCs of the insula and nucleus accumbens among subjects with Internet gaming disorder (IGD). Methods: We recruited 30 males with IGD and 30 controls and evaluated their FC using functional magnetic imaging scanning under resting, a state with relaxation, closed eyes, with inducement to think of nothing systematically, become motionless, and instructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 46 publications
2
48
1
2
Order By: Relevance
“…Impulsive behaviours are associated with deficits of frontostriatal networks, interhemispheric connectivity, and an altered structure of the insula . Dysfunction of the prefrontal cortex and disrupted frontostriatal connectivity indicate that the frontal lobe fails to regulate emotion‐driven urges .…”
Section: Resultsmentioning
confidence: 99%
“…Impulsive behaviours are associated with deficits of frontostriatal networks, interhemispheric connectivity, and an altered structure of the insula . Dysfunction of the prefrontal cortex and disrupted frontostriatal connectivity indicate that the frontal lobe fails to regulate emotion‐driven urges .…”
Section: Resultsmentioning
confidence: 99%
“…Another fMRI study found that boredom was related to the activities of insula and caudate nucleus [31]. Moreover, fMRI studies also found that inter‐hemispheric insula [32], amygdala–insula [33], amygdala–frontal [33], and frontostriatal [32] functional connections were associated with Internet gaming disorder. Insula, amygdala, and bilateral ventromedial prefrontal cortex that are responsible for emotional regulation, impulse control and motivation are involving in both boredom proneness and Internet addiction.…”
Section: Discussionmentioning
confidence: 97%
“…Higher levels of impulsivity may be associated with hedonic eating (ie, eating after energy requirements have been met) patterns (Nederkoorn, Smulders, Havermans, Roefs, & Jansen, 2006). Impairments in impulse control mechanisms contribute to many disorders, including binge eating, bulimia nervosa, drug addiction, alcoholism, and Internet gaming (Alhassoon, Sorg, Stern, Hall, & Wollman, 2015; Chen et al, 2016; Ding et al, 2014; Gearhardt, Boswell, & Potenza, 2014; Goldstein & Volkow, 2011). …”
Section: Factors That Lead To the Formation Of Famentioning
confidence: 99%